Köln Kunst 3. - Ermacora, Beate; BBK-Stapelhaus, Köln (Köln : BBK (Berufsverband Bildender Künstler), Köln, 1991)
Adochi ; Attila ; Banana, Charly ; Barow, Frauke ; Bartholomé, Monika ; Bausch, Andreas ; Becker, Krimhild ; Below, Peter ; Berent, Hella ; Beyelschmidt, Rosy ; Birgfeld, Detlef ; Breloh, Heinz ; von Brentano, Tremezza ; Bretschneider, Georgy ; de Breuyn, Jörg ; Brügger, Susanne ; etc.
Köln Kunst 3, BBK - Stapelhaus, Köln, Ausstellung vom 13.11. - 31.12.1991
boek